2016
DOI: 10.1007/978-1-4939-6393-5_14
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Wnt/β-Catenin Signaling in Skin

Abstract: Wnt signaling through β-catenin plays a crucial role in skin development and homeostasis. Disruption or hyperactivation of this pathway results in skin defects and diseases (Lim and Nusse, Cold Spring Harb Perspect Biol 5(2), 2013). Monitoring Wnt signaling in skin under normal and abnormal conditions is therefore critical to understand the role of this pathway in development and homeostasis. In this chapter, we provide methods to detect Wnt/β-catenin (canonical) signaling in the skin. We present a comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 31 publications
(26 reference statements)
0
7
0
Order By: Relevance
“…Wnt signaling through β-catenin has long been recognized to be crucial for skin epidermal development and homeostasis (32). A number of studies have confirmed that it is essential for cSCC initiation and progression, and for maintaining the cancer stem cell niche (33).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt signaling through β-catenin has long been recognized to be crucial for skin epidermal development and homeostasis (32). A number of studies have confirmed that it is essential for cSCC initiation and progression, and for maintaining the cancer stem cell niche (33).…”
Section: Discussionmentioning
confidence: 99%
“…Wnt5a is a member of the wingless-related/mouse mammary tumor virus integration family and can initiate proinflammatory responses through activation of the canonical Wnt/beta-catenin and noncanonical Wnt/Ca(2ϩ) signaling pathways. Wnt5a is restricted primarily to the basal layer in adult skin, with limited expression in the upper spinous and granular layers (34,35). VZV-infected adult skin exhibited increased Wnt5a expression (green signal) adjacent to VZV skin lesions (red signal) in the epidermal compartment (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Wnt signalling plays a critical role in regulating the proliferation, differentiation and motility of skin cells, as well as wound healing and fibrosis 52 . Wnt signalling through β ‐ catenin plays a crucial role in skin development and homeostasis 53 . Several studies have reported dysfunction of the Wnt/β‐catenin signalling pathway in patients with diabetes mellitus wounds and comorbidity in patients with HS 54 …”
Section: Discussionmentioning
confidence: 99%
“…52 Wnt signalling through b-catenin plays a crucial role in skin development and homeostasis. 53 Several studies have reported dysfunction of the Wnt/b-catenin signalling pathway in patients with diabetes mellitus wounds and comorbidity in patients with HS. 54 p53 signalling…”
Section: Wnt/b-catenin Signallingmentioning
confidence: 99%